2015
DOI: 10.1017/s002081831500020x
|View full text |Cite
|
Sign up to set email alerts
|

The Political Legacies of Combat: Attitudes Toward War and Peace Among Israeli Ex-Combatants

Abstract: Recent research has highlighted combat's positive effects for political behavior, but it is unclear whether they extend to attitudes toward the conflict itself. We exploit the assignment of health rankings determining combat eligibility in the Israel Defense Forces to examine the effect of combat exposure on support for peaceful conflict resolution. Given the centrality of the Israeli-Palestinian conflict to global affairs, and its apparent intractability, the political consequences of combat become all the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
3

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(117 citation statements)
references
References 37 publications
3
111
3
Order By: Relevance
“…47 Further analysis suggested that recruited districts were not directly targeted by investments in education, nor is there evidence of stronger demand for education in the recruited districts.…”
mentioning
confidence: 99%
“…47 Further analysis suggested that recruited districts were not directly targeted by investments in education, nor is there evidence of stronger demand for education in the recruited districts.…”
mentioning
confidence: 99%
“…Overall, the results show that terrorism is associated with a systematic increase in the frequency of content relating to right-wing ideology in Israeli books, an increase that has become more pronounced over time. These findings hold in tens of thousands of books, using Klor (2006, 2008); Gould and Klor (2010); Getmansky and Zeitzoff (2014); Grossman, Manekin and Miodownik (2015) 31 The Israeli National Election Studies (2013); The Israel Democracy Institue (2017) 32 Natanzon et al (2017) 33 Macdonald (1998); Strinati (2004) 34 Anderson (2006) 35 Gentzkow and Shapiro (2010) developed and tested a theory of the determinants of political slant public demand for right-wing content, especially since the end of the Second Intifada, have led to increased production of such content in the Israeli market for popular books.…”
Section: Resultsmentioning
confidence: 69%
“…What can account for the increasing support for hardline nationalistic worldviews in the population, even long after the Second Intifada ended and terrorist violence subsided? There are many 1 Klor (2006, 2008); Gould and Klor (2010); Getmansky and Zeitzoff (2014); Grossman, Manekin and Miodownik (2015) 2 Kibris (2011) 3 Landau et al (2004); Gershkoff and Kushner (2005) Note: The figure plots the proportion of respondents intending to vote for left-wing, center, and right-wing parties in each election from 1996 to the present. Data come from the The Israeli National Election Studies (2013).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, they find that municipalities with the highest levels of political violence are more likely to support peace referenda than municipalities with low levels of conflict exposure. Evidence from the Israeli–Palestinian conflict shows that combat experience or exposure to violence is associated with more hawkish attitudes among Israelis (Grossman, Devorah, and Miodownik, 2015; Canetti‐Nisim et al., 2009). Kibris (2011), using the Kurdish conflict in Turkey, finds that exposure to conflict makes Turkish voters “less concessionist” toward Kurdish demands.…”
Section: Conflict As a Transformative Experiencementioning
confidence: 99%